PENGARUH SYAIR PERMAINAN PET-PET NYEUT DALAM MENINGKATKAN NILAI MORAL ANAK - Nurdiana Nurdiana; Ery Waty Ery Waty; Zulkifli Zulkifli (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
Instilling moral values in children can be done through traditional games, this has been researched by Misbach (2006) from the University of Indonesia Education entitled "The Role of Educative Traditional Games in Contributing to the Formation of Moral Values and National Identity" His conclusion is "Traditional games have a very important role in the formation of moral values and national identity, traditional games rely a lot on moral values and local wisdom which are the way of life of ethnic groups where these moral values are currently starting to fade little by little”. Pet pet nyeut (hide and seek) ) is a type of traditional game in Aceh Besar. These traditional games are rarely played by children today. Whereas in these traditional gamesmany things are obtained by children, including managing strategies, sports, honesty, loyal friends and being sensitive to the surrounding environment. This has been proven by the author in the research title "The Role Of Aceh Tradisional Games In Forming The Character Of Adolescents" (2019). The results of the study "proved that through traditional games can form good character for teenagers directly"children play the traditional game of pet-pet nyeut, the moral value of honesty and hatred of lies will increase.Based on the description above, the author has developed a research entitled "Influence The Effect Of The Pet-pet Nyeut layer In Increasing the Moral Values Of Children ".